2007
DOI: 10.1525/mp.2007.25.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Local Processing Advantage in Musicians: Evidence from Disembedding and Constructional Tasks

Abstract: WHEN PROCESSING MUSIC STIMULI, MOST PEOPLE show a global bias (e.g., Evers et al., 1999). Extensive music training, however, develops both global (Halpern & Bower, 1982) and local (Burton et al., 1989) music processing abilities. Our goal was to determine whether enhancement of musicians' local processing abilities is domain-specific or extends to processing nonmusical, visual stimuli. Musicians outperformed nonmusicians on the Group Embedded Figures Test (Experiment 1) and on Block Design (Experiment 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 58 publications
5
55
3
Order By: Relevance
“…Musicians, whose training, according to the OPERA hypothesis [42], requires and nurtures the development of focused attention, have been shown to have a more local and analytical approach to music processing than non-musicians, who have a more holistic approach [42]–[45]. A more focussed and local approach to music processing means that the chord precluding harmonic resolution could have been perceived by musicians as a new incongruous element, similar to the first incongruous element.…”
Section: Discussionmentioning
confidence: 99%
“…Musicians, whose training, according to the OPERA hypothesis [42], requires and nurtures the development of focused attention, have been shown to have a more local and analytical approach to music processing than non-musicians, who have a more holistic approach [42]–[45]. A more focussed and local approach to music processing means that the chord precluding harmonic resolution could have been perceived by musicians as a new incongruous element, similar to the first incongruous element.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the investigations referred to so far, no effects on visual memory were found, other studies reported improved visual memory performance for individuals who received music training (Rauscher et al, 1995; Bilhartz et al, 1999; Costa-Giomi, 1999; Hetland, 2000; Brochard et al, 2004; Sluming et al, 2007; Stoesz et al, 2007; Jakobson et al, 2008). …”
Section: Introductionmentioning
confidence: 91%
“…Indeed, most individuals are particularly susceptible to intrusions of the global stimuli on trials in which they are to report local stimuli (Navon, 1977). Some individuals show a more local bias, however, such as individuals from collectivist cultures (Davidoff, Fonteneau, & Fagot, 2008), musicians (Stoesz, Jakobson, Kilgour, & Lewycky, 2007), individuals with obsessive-compulsive disorder (Moritz & Wendt, 2006), and individuals with autism (Scherf, Luna, Kimchi, Minshew, & Behrmann, 2008). As such, this task gives a good indication of participants' global or local bias.…”
Section: Stimuli and Designmentioning
confidence: 99%